Vitrimers based on bio-derived chemicals: overview and future prospects - Balaji Krishnakumar; Andrea Pucci; Prakash P. Wadgaonkar; Indresh Kumar; Wolfgang H. Binder; Sravendra Rana (Chemical Engineering Journal, 2022)
The perspective of using recyclable and biobased materials in the vitrimeric concept is attractive, in view of the regulatory guidelines and pressing need to reduce CO2-emissions. The expansion of viable bio-based polymeric materials is gaining increased attention to achieve sustainable development goals. Although durability, cost, and performance still limit their real life applications, these limitations can be overcome through state-of-the-art bio-vitrimeric materials displaying thermoset like mechanical and thermal properties as well as thermoplastic like malleable and thus recyclable properties. Bio-derived chemicals based vitrimers can be of advantage, where material design is made from scratch, allowing to plan material properties in line with their future life cycle from the very beginning. This article emphasizes the current needs of vitrimers based on bio-derived chemicals, including their recycling, reprocessing, and self-healing properties, along with their advantages and potential obstacles from todays’ perspective. The article also identifies potential bio-derivatives as attractive building blocks for vitrimers because of their potential for sustainability.
Keywords: Recycling; Self-healing; Sustainable materials; Vitrimers